3D numerical back-analysis of an instrumented underpass road. (25th October 2020) - Houhou, Mohamed Nabil; Belounar, Abderahim; Amari, Tamir; Brouthen, Abdelaziz
Abstract : Purpose: This paper aims to focus on three-dimensional (3D) numerical simulation of a monitored urban underground road consisting of diaphragm walls supported by one row of temporary steel struts and a cover slab in the central area. In addition to the lateral wall displacements, the analysis focuses on the load development in the struts and the evolution of the total stresses at the soil–wall interface, and highlights the 3D effect on the behavior of the structure. Design/methodology/approach: Computation by back-analysis has become an important contribution to the understanding of observed phenomena. In this context, this paper investigates a full 3D numerical back-analysis of diaphragm wall deformation using the finite difference code FLAC3D. Findings: The instrumentation allows a deep understanding of the ground response and the soil-structure interaction phenomena. It also provides an opportunity to validate numerical models. Using a soil model with simple failure criteria, the wall displacements are strongly influenced by the soil deformation modulus. The strut stiffness considerably influences the wall behavior. The geometrical effects have a significant impact on the induced wall displacements. Originality/value: In the present study, the main soil geotechnical characteristics were deduced from laboratory and in situ tests. However, Young's modulus of the soil has been adjusted to take account of the unloading effect. In the same context, the non-linearity of the elastic characteristics of the steel struts has been taken into account by modeling the struts using their experimental stiffness instead of their theoretical rigidity.